ZON-structure aluminum phosphate molecular sieve as well as synthesis method and application thereof

The ZON structure of aluminum phosphate UiO-7 molecular sieve was synthesized by the common template method, which solved the corrosiveness of fluoride in the prior art, and achieved efficient and low-cost molecular sieve synthesis, which was suitable for industrial production.

CN119528175AActive Publication Date: 2025-02-28DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311117126.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2025-02-28
Estimated Expiration
2043-08-31

AI Technical Summary

Technical Problem

The synthesis of existing UiO-7 molecular sieve requires the use of fluoride as a mineralizer, which leads to corrosive problems during the synthesis process.

Method used

The co-template method of adding seeds to the main template agent TMA+ and co-template agent co-SDA are used to form an initial gel by mixing aluminum source, water, phosphorus source, TMA+, seeds and co-SDA, and crystallize under closed conditions to obtain an aluminum phosphate UiO-7 molecular sieve with ZON structure.

Benefits of technology

The high-purity and high crystallinity UiO-7 molecular sieve was successfully synthesized, with a product yield of 30-80%, avoiding the use of fluoride, reducing costs, and suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528175A_ABST
    Figure CN119528175A_ABST
Patent Text Reader

Abstract

The invention discloses an aluminum phosphate molecular sieve with a ZON structure as well as a synthesis method and application of the aluminum phosphate molecular sieve. The synthesis method of the ZON structure aluminum phosphate molecular sieve comprises the following steps: S1, mixing an aluminum source, water, a phosphorus source, a main template agent TMA < + >, a seed crystal and a co-template agent co-SDA to obtain initial gel; tMA < + > is tetramethyl ammonium, and co-SDA is an organic amine reagent different from TMA < + >; and S2, crystallizing the initial gel in the step S1 under a closed condition to obtain the aluminum phosphate UiO-7 molecular sieve raw powder with the ZON structure. The UiO-7 molecular sieve synthesized by the method is high in crystallinity, and the yield reaches 70% or above. The molecular sieve can be used for adsorbing heat storage materials, heat pump materials, refrigeration materials or gas adsorption separation, and the effect is good; the method is simple and convenient to operate, fluoride-free, low in cost, commercially available in raw materials and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material technology, and in particular relates to a ZON structure aluminum phosphate molecular sieve and a synthesis method and application thereof. Background Art

[0002] Aluminum phosphate (AlPO) molecular sieve originated in 1982 and was first synthesized by Union Carbide Corp. As one of the important members of molecular sieve materials, AlPO molecular sieve has outstanding performance in the fields of catalyst support, adsorption separation, adsorption energy storage, etc. due to its regular pores, rich pore distribution and excellent stability. For example, AlPO-11 (AEL) can support Pt for isomerization reaction of alkanes, AlPO-42 (LTA) and EMM-8 (SFO) have outstanding performance in the field of water adsorption energy storage, and ULM-6 has an adsorption selectivity of 15.5 and 29.1 in CO2 / CH4 and CO2 / N2, respectively. The AlPO skeleton can be regarded as a three-dimensional skeleton formed by [AlO4] and [PO4] connected by shared oxygen bridges. The Al / P of the skeleton is ≈ 1, which is a neutral skeleton. Therefore, the performance of AlPO materials in the field of adsorption usually depends on the structure.

[0003] At present, in the field of CH4 / N2 adsorption and separation, small-pore UiO-7 (ZON structure, 8 / 6 / 4-membered ring) molecular sieves have shown considerable adsorption capacity and separation ratio. However, the synthesis of UiO-7 always requires the use of fluoride (tetramethylammonium fluoride or hydrofluoric acid) as a mineralizer, and the template agent is usually tetramethylammonium hydroxide (TMAOH). Fluoride is highly corrosive to synthesis equipment. Summary of the invention

[0004] In view of the above problems, the present invention provides a ZON structure aluminum phosphate molecular sieve and a synthesis method and application thereof, which can solve the technical problem of fluoride corrosiveness in the molecular sieve synthesis process.

[0005] In one aspect, the present invention provides a method for synthesizing a ZON structure aluminum phosphate molecular sieve, the method comprising the following steps:

[0006] S1: Aluminum source, water, phosphorus source, main template TMA + , seed crystals and co-template agent co-SDA are mixed to obtain an initial gel;

[0007] Among them, TMA + It is a tetramethylammonium compound. Co-SDA is different from TMA. + Organic amine reagents;

[0008] S2: The initial gel in step S1 is crystallized under closed conditions to obtain aluminum phosphate UiO-7 molecular sieve raw powder with a ZON structure.

[0009] Optionally, in step S1, the aluminum source, water, phosphorus source, and primary template agent TMA in the initial gel + The molar ratio of co-template co-SDA is:

[0010] Al2O3:H2O:P2O5:TMA + :co-SDA=0.5~1.5:10~100:0.5~1.5:0.5~2.0:0~2.0;

[0012] The molar number of the aluminum source is calculated as the molar number of Al2O3, the molar number of water is calculated as the molar number of H2O itself, the molar number of the phosphorus source is calculated as the molar number of P2O5, and the main template agent TMA is calculated as follows: + The number of moles of TMA + The moles of the co-template agent co-SDA are calculated based on their own moles.

[0013] Optionally, in step S1, the aluminum source, water, phosphorus source, and primary template agent TMA in the initial gel + The molar ratio of co-template co-SDA is:

[0014] Al2O3:H2O:P2O5:TMA + :co-SDA=0.8~1.2:20~100:0.8~1.2:0.8~2.0:0.5~2.0.

[0016] Optionally, in step S1, the aluminum source, water, phosphorus source, and primary template agent TMA in the initial gel + The molar ratio of co-template co-SDA is:

[0017] Al2O3:H2O:P2O5:TMA + :co-SDA=1.0:40~60:1.0:0.5~1.0:1.0~1.5.

[0019] Optionally, in step S1, the amount of the seed crystal added is 1 to 20 wt % of the total mass of Al2O3 and P2O5.

[0020] Optionally, in step S1, the amount of the seed crystal added is 5 to 20 wt % of the total mass of Al2O3 and P2O5.

[0021] Optionally, in step S1, the amount of the seed crystal added is selected from any value among 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, or any range between two of them.

[0022] Optionally, the seed crystals are selected from UiO-7 seed crystals.

[0023] The UiO-7 seed crystals in step S1 of the present invention can be synthesized by existing methods, or the molecular sieve raw powder synthesized in steps S1 and S2 can be used, and the molecular sieve raw powder can also be used as seed crystals after being calcined.

[0024] Optionally, in step S1, the primary template agent TMA + At least one selected from tetramethylammonium hydroxide (TMAOH), tetramethylammonium chloride (TMACl), tetramethylammonium bromide (TMACl) and tetramethylammonium iodide (TMAI).

[0025] Optionally, in step S1, the co-template agent co-SDA is selected from at least one of dimethylamine, trimethylamine, diethylamine, triethylamine, tetraethylammonium hydroxide, propylamine, dipropylamine, tripropylamine, diisopropylamine, n-butylamine, morpholine, piperazine, tetramethylethylenediamine, cyclohexylamine, cycloheximide, diethanolamine and 1-[2-(2-hydroxyethoxy)ethyl]piperazine.

[0026] Preferably, the co-template agent co-SDA is at least one selected from diethylamine, morpholine, triethylamine, dipropylamine and n-butylamine.

[0027] Optionally, in step S1, when the primary template agent TMA + When the initial gel contains at least one of tetramethylammonium bromide, tetramethylammonium chloride and tetramethylammonium iodide, the aluminum source, water, phosphorus source, primary template agent TMA + The molar ratio of co-template co-SDA is:

[0028] Al2O3:H2O:P2O5:TMA + :co-SDA=0.5~1.5:10~100:0.5~1.5:0.5~2.0:0.5~2.0.

[0030] That is, when the TMA in the initial gel of the present invention + When one or a combination of TMACl, TMACl and TMAI is used, the molar ratio of co-SDA in the initial gel must be no less than 0.5 (greater than or equal to 0.5) to synthesize the molecular sieve.

[0031] The present invention adopts the main template agent TMA + The yield of UiO-7 obtained by the co-template agent co-SDA plus seed (co-template method) synthesis method is usually greater than 70wt%.

[0032] Optionally, in step S1, when the amount of the co-template co-SDA added is 0, the main template TMA + is tetramethylammonium hydroxide, and the molar ratio of each component in the initial gel is: Al2O3:H2O:P2O5:TMA + =0.5~1.5:10~100:0.5~1.5:1.5~2.0, and the added amount of the seed crystal is 1~20wt% of the total mass of Al2O3 and P2O5; the seed crystal is selected from UiO-7 seed crystal.

[0033] That is, when the amount of co-SDA added to the initial gel of the present invention is 0, TMA + When TMAOH (TMAOH+seed crystals) is selected, the molar ratio of TMAOH in the initial gel is not less than 1.5 (greater than or equal to 1.5), and under the condition of seed crystal addition, UiO-7 can also be synthesized and the product yield is about 30wt%.

[0034] Optionally, in step S1, the aluminum source is selected from at least one of pseudo-boehmite, alumina, aluminum hydroxide, aluminum isopropoxide, aluminum sec-butoxide, aluminum phosphate and aluminum chloride.

[0035] Preferably, the aluminum source is selected from at least one of pseudo-boehmite, aluminum hydroxide, aluminum isopropoxide and aluminum oxide.

[0036] Optionally, in step S1, the phosphorus source is selected from at least one of orthophosphoric acid, phosphorous acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphorus oxides, organophosphorus reagents and aluminum phosphate.

[0037] Preferably, the phosphorus source is orthophosphoric acid.

[0038] Optionally, in step S1, the aluminum source, the water, the phosphorus source and the primary template agent TMA + Premixing to obtain a mixture I; the mixture I is then mixed with the seed crystal and the co-template agent co-SDA to obtain an initial gel.

[0039] Preferably, the premixing is stirred for 2 hours.

[0040] Optionally, in step S2, the initial gel is transferred to a self-pressure reactor and crystallized at 140-200° C. for 1-24 h. The product is washed, centrifuged and dried to obtain UiO-7 raw powder.

[0041] Optionally, the crystallization method is dynamic or static.

[0042] Optionally, in step S2, the crystallization temperature is 150-200° C., the crystallization time is 2-12 h, and the crystallization method is dynamic crystallization.

[0043] Optionally, the crystallization temperature is selected from any value of 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, or any range therebetween.

[0044] Optionally, the crystallization time is selected from any value of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24 hours or any range between two of them.

[0045] Optionally, in step S2, the UiO-7 molecular sieve raw powder is calcined in an air atmosphere at a temperature of 450-800° C. to remove the template.

[0046] Optionally, the UiO-7 molecular sieve is calcined at a temperature of 550-800° C. for 4-10 hours.

[0047] Optionally, the calcining temperature is selected from any value of 450, 500, 550, 600, 650, 700, 750, 800° C. or any range therebetween.

[0048] In the present invention, the UiO-7 molecular sieve prepared according to the above steps is calcined at 550-800° C. for 4-10 hours to remove the template agent, and is used for subsequent H2O / CH4 / N2 / CO2 adsorption performance tests.

[0049] In a second aspect, the present invention provides a ZON structure aluminum phosphate molecular sieve, which is synthesized using the above method.

[0050] In a third aspect, the present invention provides a molecular sieve synthesized by the above method or the use of the above molecular sieve in adsorption heat storage materials, heat pump materials, refrigeration materials or gas adsorption separation.

[0051] Compared with the prior art, the present invention has the following beneficial effects:

[0052] 1) The present invention successfully synthesized an aluminum phosphate molecular sieve UiO-7 with high purity and high crystallinity.

[0053] 2) The present invention adopts a seed crystal method to synthesize aluminum phosphate molecular sieve UiO-7 having a ZON structure. The method has a yield of 30-80%, is easy to operate, is fluorine-free, has low cost, and has commercially available raw materials, which is suitable for industrial production;

[0054] 3) The aluminum phosphate molecular sieve UiO-7 with a ZON structure synthesized by the present invention can be used for adsorption heat storage materials, heat pump materials, refrigeration materials or adsorbents to separate gases, and has a good adsorption capacity for CH4 and N2. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 The XRD patterns of the products of Examples 1-3 of the present invention;

[0056] Figure 2 This is a SEM photo of the product of Example 1 of the present invention;

[0057] Figure 3 It is the N2 physical adsorption isotherm of the products of Examples 1-2 and Comparative Example 1 of the present invention;

[0058] Figure 4 It is the CH4 static adsorption isotherm (25°C) of the products of Examples 1-2 and Comparative Example 1 of the present invention;

[0059] Figure 5 It is the N2 static adsorption isotherm (25°C) of the products of Examples 1-2 and Comparative Example 1 of the present invention;

[0060] Figure 6 This is a SEM photo of the product of Example 2 of the present invention;

[0061] Figure 7 This is a SEM photo of the product of Example 3 of the present invention;

[0062] Figure 8 The XRD diagram of the product of comparative example 1-3 of the present invention;

[0063] Fig. 9 This is a SEM photograph of the product of Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0064] The present application is further described below in conjunction with specific embodiments. The following are only a few embodiments of the present application, and are not intended to limit the present application in any form. Although the present application discloses the following preferred embodiments, they are not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the above disclosed technical content to make some changes or modifications are equivalent to equivalent implementation cases and are within the scope of the technical solution.

[0065] The chemical reagents used in the embodiments of the present invention can be purchased through commercial channels without secondary purification. The English abbreviations of the chemical reagents used in the embodiments are as follows:

[0066] Morpholine (Mor), diethylamine (DEA), triethylamine (TEA), dipropylamine (DPA), tetramethylammonium hydroxide (TMAOH), tetramethylammonium chloride (TMACl), tetramethylammonium bromide (TMABr), tetramethylammonium iodide (TMAI).

[0067] The calculation formula for product yield in the embodiment is as follows:

[0068] Yield=0.8·m product / (m Al2O3 +m P2O5 +m seed )×100%;

[0069] 0.8—The empirical value of inorganic content in the original powder solid obtained by thermogravimetric analysis;

[0070] m product —The solid mass of the product obtained after washing, separation and drying;

[0071] m Al2O3 —The mass of Al2O3 corresponding to the aluminum source in the initial gel;

[0072] m P2O5 —The mass of P2O5 corresponding to the phosphorus source in the initial gel;

[0073] m seed —The mass of the seeds introduced into the initial gel;

[0074] The amount of seed crystal introduced in all embodiments of the present invention is uniformly expressed as x·m (Al2O3+P2O5) ; where x represents the ratio of the added seed to the total mass of Al2O3 and P2O5 in the initial gel, m (Al2O3+P2O5) is the mass sum of Al2O3 and P2O5 corresponding to the initial gel. The amount of seed crystals introduced in the examples is represented by x only.

[0075] The crystal structure of the embodiment of the present invention is identified by powder X-ray diffraction (XRD) results. The XRD test instrument is an X'Pert PRO X-ray diffraction analyzer manufactured by PANalytical of the Netherlands, with a Cu target, a Kα emission source (wavelength 0.15418 nm), and operating parameters of 40 kV voltage and 40 mA current.

[0076] The sample morphology of the embodiment of the present invention is obtained by scanning electron microscopy (SEM), and the testing instrument is Hitachi SU8020 field emission scanning electron microscope (FE-SEM) with an acceleration voltage of 2KV.

[0077] The specific surface area, pore volume and other parameters of the sample in the embodiment of the present invention are obtained using the ASAP2020 physical adsorption instrument of Micromeritics, USA. The high-temperature calcined sample is vacuum treated at 350°C for 4 hours, and the effective volume of the sample tube is measured by He. N2 is the adsorbed gas. Physical adsorption and desorption experiments are carried out in a liquid nitrogen (77K) environment. The specific surface area of ​​the sample is calculated using the BET equation, and the total pore volume of the sample is estimated using the N2 adsorption amount at a relative pressure (P / P0) of 0.99. The t-plot model is used to obtain the micropore surface area and volume, and the cross-sectional area of ​​the N2 molecule is 0.162nm 2 , the surface area, volume and diameter of the pores were obtained by the BET-BJH method.

[0078] The adsorption isotherm data of CH4 and N2 of the samples in the embodiment of the present invention were obtained by a 3FLEX physical adsorption instrument of Micromeritics, USA, and the test temperature was 25° C. Before the test, about 0.2 g of the sample was treated in a vacuum environment at 350° C. for 4 hours.

[0079] Example 1 (TMAOH+Mor+seed)

[0080] The initial gel molar ratio of UiO-7 is Al2O3:H2O:P2O5:TMAOH:Mor=1.0:40.0:1.0:0.5:1.0. Pseudo-boehmite (77%), water, phosphoric acid (85% H3PO4), TMAOH (25% aqueous solution) are added in sequence and stirred for about 2 hours. After being mixed evenly, UiO-7 seed crystals with x=0.15 are added, and finally Mor is added. After stirring for about 2 hours, the obtained initial gel is transferred to a reactor and dynamically crystallized at 180°C for about 2 hours. After washing, separating and drying the obtained product, the molecular sieve raw powder is obtained with a yield of 75%.

[0081] The product phase was identified by XRD ( Figure 1 ), there are obvious diffraction peaks near 2θ=10.7314°, 13.5538°, 19.9928°, 21.0599°, 23.3511°, 30.0644°, and no other impurity peaks appear. Combined with the SEM results ( Figure 2 ) can be proved to be pure phase UiO-7, and SEM results show that its morphology is a bipyramidal shape with a diameter of about 300nm.

[0082] The N2 adsorption results of the samples after calcination at 600℃ for 6h ( Figure 3 ) is S BET =270.5m 2 / g,S micro =247.2m 2 / g,Vtotal =0.2305cm 3 / g,V micro =0.1285cm 3 / g. Under the condition of 25℃, the saturated adsorption capacity of CH4 reached 0.7mmol / g, and the adsorption capacity of N2 also exceeded 0.2mmol / g ( Figure 4 and Figure 5 ).

[0083] Example 2 (TMABr+DEA+seed crystal)

[0084] The initial gel molar ratio of UiO-7 is Al2O3:H2O:P2O5:TMABr:DEA=1.0:60.0:1.0:0.5:1.0. Aluminum hydroxide (99%), water, phosphoric acid (85% H3PO4) and TMAOH (25% aqueous solution) are added in sequence, and after the above raw materials are evenly mixed, UiO-7 seed crystals with x=0.10 are added, and finally DEA is added. After stirring for about 2 hours, it is transferred to a reactor and dynamically crystallized at 150°C for about 4 hours. After washing, separation and drying the obtained product, the molecular sieve raw powder is obtained with a yield of 72%.

[0085] The product phase was identified by XRD ( Figure 1 ), similar to the XRD peak shape of the sample in Example 1, no other impurity peaks appear, combined with the SEM results ( Figure 6 ) can be proved to be pure phase UiO-7, and SEM results show that its morphology is a bipyramidal shape with a diameter of about 300nm.

[0086] The results of N2 physical adsorption after the sample was calcined at 600℃ for 6h ( Figure 3 ) is: S BET =268.7m 2 / g,S micro =247.8m 2 / g,V total =0.2126cm 3 / g,V micro =0.1288cm 3 / g. The CH4 and N2 adsorption results are similar to those in Example 1, and the single component adsorption amounts are both higher than those in Comparative Example 1 ( Figure 4 and Figure 5 ).

[0087] Example 3 (TMAOH + seed crystal)

[0088] The initial gel molar ratio of UiO-7 is Al2O3:H2O:P2O5:TMAOH=1.0:40.0:1.0:1.5. Pseudoboehmite (67.5%), water, phosphoric acid (85% H3PO4), TMAOH (25%) are added to a beaker in sequence, followed by the addition of a seed crystal of x=0.2. After all the above raw materials are fully mixed, they are transferred to a reactor and dynamically crystallized at 180°C for 5 hours. The product is washed, separated, and dried to obtain the product raw powder.

[0089] The samples were subjected to XRD ( Figure 1 ) analysis, similar to the product of Example 1-2, the yield is 30%, which is lower than that of Examples 1 and 2. The SEM results of the sample are as follows Figure 7 As shown, the product has uniform morphology and the grain size is about 200-300nm.

[0090] Examples 4 to 12 (TMA + +co-SDA+seed crystal)

[0091] The initial gel was prepared by referring to the formulation method of Example 1. The types and proportions of raw materials and crystallization conditions are detailed in Table 1. The products were all UiO-7 after phase identification by XRD.

[0092] The calcined crystals of the molecular sieve raw powder synthesized in Example 1 were used as UiO-7 seed crystals in Example 4, and Example 4 adopted a static crystallization method; the seed crystals used in Examples 5 to 12 were all the molecular sieve raw powder synthesized in Example 1.

[0093] Table 1. Raw material molar composition and crystallization conditions for the synthesis of UiO-7 molecular sieve

[0094]

[0095]

[0096] Comparative Example 1 (TMAOH+HF)

[0097] The initial gel was prepared according to the molar ratio of Al2O3:H2O:P2O5:TMAOH:HF=1.0:50.0:1.0:1.5:0.5. The raw materials were pseudo-boehmite (67.5%), orthophosphoric acid (85% H3PO4), tetramethylammonium hydroxide (25% aqueous solution), and hydrofluoric acid (49% aqueous solution). The above raw materials were added in sequence and mixed evenly, transferred to a self-pressure reactor, and dynamically crystallized at 150°C for 24 hours. The product was washed, separated, and dried to obtain UiO-7 raw powder.

[0098] The XRD results of the product are as follows Figure 8 As shown, the SEM results are Fig. 9As shown, the XRD results of the product are consistent with those of Example 1 and Example 2, but the morphology is obviously different.

[0099] The results of N2 physical adsorption after the sample was calcined at 600℃ for 6h ( Figure 3 ) is: S BET =302.2m 2 / g,S micro =242.0m 2 / g,V total =0.3355cm 3 / g,V micro =0.1232cm 3 / g. The adsorption of CH4 and N2 by this sample is not as good as that of Example 1 and Example 2 ( Figure 4 and Figure 5 ).

[0100] Comparative Example 2 (TMAOH+Mor)

[0101] Referring to the initial gel molar ratio, raw material types and crystallization conditions of Example 1, no seed crystals were introduced, and the XRD results ( Figure 8 ) proves that the product synthesized in Comparative Example 2 contains two structures, AFN and SOD, and no diffraction peak of the ZON structure appears, which proves that UiO-7 seed is the key factor in achieving fluorine-free synthesis of the molecular sieve.

[0102] Comparative Example 3 (TMAOH + Seed)

[0103] The proportion, ingredients and crystallization method of the synthetic gel were the same as those of Example 9, except that no co-SDA was added and the product was washed, separated and dried. The XRD results showed that only the diffraction peak of the SOD structure appeared ( Figure 8 ); It shows that the use of co-SDA template can promote the crystallization of UiO-7 molecular sieve. At the same time, when there is no co-SDA and the amount of TMAOH added is less than or equal to 1.0, the ideal UiO-7 molecular sieve product cannot be obtained.

[0104] In Example 3 of the present invention, the ideal UiO-7 molecular sieve can be successfully synthesized without co-SDA and when the amount of TMAOH added is 1.5, but the yield is 30%, indicating that co-SDA can not only reduce the main template TMA + The dosage can also increase the product yield.

[0105] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for synthesizing a ZON structure aluminum phosphate molecular sieve, characterized in that: The synthesis method comprises the following steps: S1: Aluminum source, water, phosphorus source, main template TMA + , seed crystals and co-template agent co-SDA are mixed to obtain an initial gel; Among them, TMA + It is a tetramethylammonium compound. Co-SDA is different from TMA. + Organic amine reagents; S2: The initial gel in step S1 is crystallized under closed conditions to obtain aluminum phosphate UiO-7 molecular sieve raw powder with a ZON structure.

2. The method for synthesizing a ZON structure aluminum phosphate molecular sieve according to claim 1, characterized in that: In step S1, the aluminum source, water, phosphorus source, and primary template TMA in the initial gel + The molar ratio of co-template co-SDA is: <h2 style=";text-align:left;direction:ltr">Al2O3:H2O:P2O5:TMA<h2 style=";text-align:left;direction:ltr"> + <h2 style=";text-align:left;direction:ltr"> :co-SDA=0.5~1.5:10~100:0.5~1.5:0.5~2.0:0~2.0; The molar number of the aluminum source is calculated as the molar number of Al2O3, the molar number of water is calculated as the molar number of H2O itself, the molar number of the phosphorus source is calculated as the molar number of P2O5, and the main template agent TMA is calculated as follows: + The number of moles of TMA + The moles of the co-template agent co-SDA are calculated based on their own moles.

3. The method for synthesizing a ZON structure aluminum phosphate molecular sieve according to claim 1, characterized in that: In step S1, the amount of the seed crystal added is 1 to 20 wt% of the total mass of Al2O3 and P2O5, and the seed crystal is selected from UiO-7 seed crystal.

4. The method for synthesizing a ZON structure aluminum phosphate molecular sieve according to claim 1, characterized in that: In step S1, the primary template agent TMA + At least one selected from tetramethylammonium hydroxide, tetramethylammonium bromide, tetramethylammonium chloride and tetramethylammonium iodide; Preferably, in step S1, the co-template agent co-SDA is selected from at least one of dimethylamine, trimethylamine, diethylamine, triethylamine, tetraethylammonium hydroxide, propylamine, dipropylamine, tripropylamine, diisopropylamine, n-butylamine, morpholine, piperazine, tetramethylethylenediamine, cyclohexylamine, cycloheximide, diethanolamine and 1-[2-(2-hydroxyethoxy)ethyl]piperazine.

5. The method for synthesizing a ZON structure aluminum phosphate molecular sieve according to claim 1, characterized in that: In step S1, when the primary template agent TMA + When the initial gel contains at least one of tetramethylammonium bromide, tetramethylammonium chloride and tetramethylammonium iodide, the aluminum source, water, phosphorus source, primary template agent TMA + The molar ratio of co-template co-SDA is: <h2 style=";text-align:left;direction:ltr">Al2O3:H2O:P2O5:TMA<h2 style=";text-align:left;direction:ltr"> + <h2 style=";text-align:left;direction:ltr"> :co-SDA=0.5~1.5:10~100:0.5~1.5:0.5~2.0:0.5~2.0。 6. The method for synthesizing a ZON structure aluminum phosphate molecular sieve according to claim 1, characterized in that: In step S1, when the amount of the co-template co-SDA added is 0, the main template TMA + is tetramethylammonium hydroxide, and the molar ratio of each component in the initial gel is: Al2O3:H2O:P2O5:TMA + =0.5~1.5:10~100:0.5~1.5:1.5~2.

0.

7. The method for synthesizing a ZON structure aluminum phosphate molecular sieve according to claim 1, characterized in that: In step S1, the aluminum source is selected from at least one of pseudo-boehmite, alumina, aluminum hydroxide, aluminum isopropoxide, aluminum sec-butoxide, aluminum phosphate and aluminum chloride; Preferably, in step S1, the phosphorus source is selected from at least one of orthophosphoric acid, phosphorous acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphorus oxides, organophosphorus reagents and aluminum phosphate.

8. The method for synthesizing a ZON structure aluminum phosphate molecular sieve according to claim 1, characterized in that: In step S1, the aluminum source, the water, the phosphorus source and the primary template agent TMA + premixing to obtain a mixture I; and mixing the mixture I with the seed crystal and the co-template agent co-SDA to obtain the initial gel; Preferably, in step S2, the crystallization temperature is 140-200° C., the crystallization time is 1-24 hours, and the crystallization method is dynamic or static; Preferably, in step S2, the UiO-7 molecular sieve raw powder is calcined in an air atmosphere at a temperature of 450-800° C. to remove the template.

9. A ZON structure aluminum phosphate molecular sieve, characterized in that: The molecular sieve is a UiO-7 molecular sieve synthesized by the method described in any one of claims 1 to 8.

10. Use of the molecular sieve synthesized by the method according to any one of claims 1 to 8 or the molecular sieve according to claim 9 in adsorption heat storage materials, heat pump materials, refrigeration materials or gas adsorption separation.

Citation Information

Patent Citations

  • Ionothermal preparation method for rare earth-substituted ZON-structured aluminophosphate molecular sieve UiO-7

    CN102730713A

  • Method for preparing high-stability mesoporous molecular sieve containing rare earth heteroatom

    CN104891524A

  • Preparation method of DNL-1 molecular sieve

    CN109574036A

  • Forming method of phosphorus-aluminum molecular sieve

    CN115924933A